Annealing‐Free Cr2O3 Electron‐Selective Layer for Efficient Hybrid Perovskite Solar Cells. Issue 3 (9th January 2018) - Dong, Jia; Wu, Jihuai; Jia, Jinbiao; He, Xin; Lan, Zhang; Fan, Leqing; Lin, Jianming; Huang, Miaoliang
Abstract: The electron‐selective layer (ESL) plays a pivotal role in the performance of perovskite solar cells (PSCs). In this study, amorphous dispersible chromium oxide (Cr2 O3 ) nanosheets are synthesized by a facile solvothermal reaction, and a Cr2 O3 ESL is prepared by spin‐coating Cr2 O3 ink on fluorine‐doped tin oxide substrates without need for further annealing. By using Cr2 O3 as the electron‐selective layer and Cs0.05 (MA0.17 FA0.83 )0.95 Pb(I0.83 Br0.17 )3 as the light‐absorption layer, a planar hybrid perovskite solar cell is fabricated. The spin‐coating speed is optimized, the structure and morphology of samples are observed, the photoelectrical properties of ESLs are characterized, and the photovoltaic behaviors of devices are measured. Results show that the as‐prepared Cr2 O3 layer has high optical transmittance and superb electron extraction and carrier transport property. The planar hybrid PSC based on the optimized Cr2 O3 ESL achieves a power conversion efficiency of 16.23 %, which is comparable to devices based on a conventional high‐temperature‐calcined TiO2 ESL. These results demonstrate a low‐cost and facile route to highly effective perovskite solar cells. Abstract : Between the sheets : Amorphous dispersible chromium oxide (Cr2 O3 ) nanosheets are synthesized by a facile solvothermal reaction. A planar hybrid perovskite solar cell based on the Cr2 O3 electron‐selective layer and Cs0.05 (MA0.17 FA0.83 )0.95 Pb(I0.83 Br0.17 )3 light‐absorption layer achieves a power conversion eﬃciency of 16.23 %, which is comparable with the device based on conventional high‐temperature‐calcined TiO2 electron‐selective layer.